Estudio de factibilidad para el montaje y puesta en marcha de una planta procesadora de café gourmet tostado y molido en el municipio de Génova Quindío (2009)
The present project has been created with the purpose of choosing the title as Business Administrator of the University of Quindío. The essential object of same is to study the feasibility of the assembly and commissioning of a plant gourmet coffee processor in the municipality of Genoa Quindío, is a study of descriptive type using a deductive method. This work presents a first chapter in which reference is made to the preliminary project required for the presentation of the same.